2013
DOI: 10.4081/gh.2013.85
|View full text |Cite
|
Sign up to set email alerts
|

Identifying inequitable exposure to toxic air pollution in racialized and low-income neighbourhoods to support pollution prevention

Abstract: Abstract.Numerous environmental justice studies have confirmed a relationship between population characteristics such as low-income or minority status and the location of environmental health hazards. However, studies of the health risks from exposure to harmful substances often do not consider their toxicological characteristics. We used two different methods, the unit-hazard and the distance-based approach, to evaluate demographic and socio-economic characteristics of the population residing near industrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…In addition, many environmental studies conducted using incident cases of leukemia have noted possible under ascertainment (Daniels and Schubauer-Berigan, 2011). It is often the case that higher concentrations of NO 2 are related to a greater density in the road network and higher volumes of traffic (Beckerman et al, 2008) and these areas more often than not comprise people in lower socioeconomic groups (Kershaw et al, 2013). Thus, underascertainment of leukemia in lower socioeconomic populations who experience higher exposures to air pollution may be responsible for this effect.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, many environmental studies conducted using incident cases of leukemia have noted possible under ascertainment (Daniels and Schubauer-Berigan, 2011). It is often the case that higher concentrations of NO 2 are related to a greater density in the road network and higher volumes of traffic (Beckerman et al, 2008) and these areas more often than not comprise people in lower socioeconomic groups (Kershaw et al, 2013). Thus, underascertainment of leukemia in lower socioeconomic populations who experience higher exposures to air pollution may be responsible for this effect.…”
Section: Discussionmentioning
confidence: 98%
“…In the vast variety of studies covering environmental justice issues each one tends to emphasize findings from a specific thematic field. However, while a great share of studies employ spatial data at some point of their analysis (e.g., [17,30,31]), some scholars criticize that frequently spatial data are not used correctly, which then leads to analyses being characterized as "essentially aspatial" [32,33]. They point out that the chosen spatial entities do not represent a suitable entity for analyzing fine scale local characteristics and disparities.…”
Section: Spatial Scale In Environmental Justice Researchmentioning
confidence: 99%
“…Environmental justice research studies which focused on air pollutants identified stronger exposures of low-income or racialized neighborhoods in Canada (e.g., [30]), Great Britain (e.g., [16]), and Germany (e.g., [18]). In a most recent study Collins et al [91] were able to find that the exposure towards air pollution might also be dependent on the sexual orientation which might in turn be linked to social discrimination.…”
Section: Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…The association between urbanization and violence might specifically operate through rapid and accelerated growth of cities (World Bank, 2011), which in turn causes disrupted infrastructure with deteriorated living standards, inequitable exposures to toxic air pollution, increased weapon availability, and youth unemployment (Cassidy et al, 2014;Patel and Burkle, 2012;Kershaw et al, 2013). a recent field study on urban violence in several countries (i.e., kenya, south africa, haiti, brazil, timor-leste) demonstrated that so called "no go zones" emerge in certain neighborhoods with concentrated poverty and social exclusion, where poor and marginalized individuals become stuck in vicious cycles of poverty and violence (World Bank, 2011).…”
Section: Rapid Urbanization Increased Air Pollution Violence and Hementioning
confidence: 99%